2008
DOI: 10.1159/000114288
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Potato Flakes Affects Cecal Short-Chain Fatty Acids, Microflora and Fecal Bile Acids in Rats

Abstract: Background/Aims: Feeding rats potato resistant starch improves large bowel health; however, there is little information on the physiological effects of preprocessed starch like potato flakes in animal experiments. The present study was designed to investigate the effects of the consumption of various colored potato (white, red and purple) flakes on cecal fermentation and fecal bile acid excretions in rats. Methods: The control group was fed a basal diet (BD) containing α-cornstarch for 4 weeks. The potato flak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…To conclude, the sufficient number of animals estimated in advance should be prepared in further studies. In our previous study, feeding rats with resistant starch from potatoes did not increase cecal propionate levels but improved plasma Chol levels [4,31]. These results suggest that cecal propionate is not necessarily essential for improving Chol levels by DF.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…To conclude, the sufficient number of animals estimated in advance should be prepared in further studies. In our previous study, feeding rats with resistant starch from potatoes did not increase cecal propionate levels but improved plasma Chol levels [4,31]. These results suggest that cecal propionate is not necessarily essential for improving Chol levels by DF.…”
Section: Discussionmentioning
confidence: 77%
“…These results indicate that T-RFLP was not sensitive to even identification of genus. Further, this technique could not Values are mean ± SEM of six rats ( * P<0.05 vs. CT) a Area percentage of Lactobacillus gallinarum GPB Gammaproteobacteria detect the number of bacteria or size of bacterial community, although potatoes in diets were suggested to increase in the total number of intestinal bacteria and the consequent cecal weight [31,32]. These findings indicate that T-RFLP may not show detailed bacterial profiles and should be exploited with other analytical techniques, such as germ culture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a lower glycemic response, other potential health benefits have been reported for potato-based RS. RS-rich potato flakes were found to increase SCFA production and fecal bile acid secretion in a rodent model (22). Longer terms studies (4-14 wk) in pigs fed raw potato starch (RS2) reported similar increases in SCFA production/concentration, and improvements in colonic length and mucosal integrity were observed (23,24).…”
Section: Food-processing Technologies For Leveraging White Potato Rs mentioning
confidence: 92%
“…Thus, we recommend more studies in animals and humans to confirm the effect of these oils on intestinal microflora. The results might lead us to recommend including special oils in diets of patients with colitis.The interactions between diet and microflora have been investigated in various studies [1] . Some recent studies indicate that probiotics can ameliorate the inflammation in colitis [1,2] .…”
mentioning
confidence: 99%
“…Some recent studies indicate that probiotics can ameliorate the inflammation in colitis [1,2] . On the other hand, there are reports which have shown that n-3 fatty acids can attenuate the inflammation of colitis, but there is no study evaluating the interaction between these fatty acids and probiotics in the intestinal environment.…”
mentioning
confidence: 99%